Transcriptomic responses of Solanum dulcamara to natural and simulated herbivory. (30th May 2017) - Lortzing, Tobias; Firtzlaff, Vivien; Nguyen, Duy; Rieu, Ivo; Stelzer, Sandra; Schad, Martina; Kallarackal, Jim; Steppuhn, Anke
Abstract: Plants are attacked by diverse herbivores and respond with manifold defence responses. To study transcriptional and other early regulation events of these plant responses, herbivory is often simulated to standardize the temporal and spatial dynamics that vary tremendously for natural herbivory. Yet, to what extent such simulations of herbivory are able to elicit the same plant response as real herbivory remains largely undetermined. We examined the transcriptional response of a wild model plant to herbivory by lepidopteran larvae and to a commonly used herbivory simulation by applying the larvae's oral secretions to standardized wounds. We designed a microarray for Solanum dulcamara and showed that the transcriptional responses to real and to simulated herbivory by Spodoptera exigua overlapped moderately by about 40%. Interestingly, certain responses were mimicked better than others; 60% of the genes upregulated but not even a quarter of the genes downregulated by herbivory were similarly affected by application of oral secretions to wounds. While the regulation of genes involved in signalling, defence and water stress was mimicked well by the simulated herbivory, most of the genes related to photosynthesis, carbohydrate‐ and lipid metabolism were exclusively regulated by real herbivory. Thus, wounding and application of oral secretions decently mimics herbivory‐induced defence responses but likely not the reallocation of primary metabolites induced by real herbivory.